Glycocalyx analysis of bladder cancer: three-dimensional images in electron microscopy and vicia villosa lectin as a marker for invasiveness in frozen sections - Enomoto, Torai; Okada, Hideshi; Tomita, Hiroyuki; Iinuma, Koji; Nakane, Keita; Tobisawa, Yuki; Hara, Akira; Koie, Takuya (Frontiers in Cell and Developmental Biology, 2024)
The abnormal glycocalyx (GCX) on the surface of cancer cells has been reported to be tall and aberrantly glycosylated and has been linked to the progression and spread of cancer-a finding also observed in bladder cancer. However, the characteristics of GCX in various types of human bladder cancer remain unknown, and herein, we aimed to provide information on the diversity of glycan components in the GCX of bladder cancers and to shed light on their characteristics. We used scanning electron microscopy and lanthanum staining to examine the surface GCX of human bladder carcinomas in three-dimensional images, showing the bulky GCX in some carcinomas. We also examined glycan alterations in early to progressive stages of bladder cancers using 20 distinct lectin stains on frozen sections from transurethral resection of bladder tumors. Distinctive Vicia villosa lectin (VVL) staining was observed in invasive urothelial carcinomas, including those with muscle invasion and variant components. In the clinical setting, cancers with atypia of grades 2-3 had a significantly higher VVL scoring intensity than those with grade 1 atypia (P < 0.005). This study identified that a specific lectin, VVL, was more specific to invasive urothelial carcinomas. This lectin, which selectively binds to sites of cancer progression, is a promising target for drug delivery in future clinical investigations.